Mobile office system oriented to intelligent terminal - Boxuan LV; Jingwen LIU; Wei XU; Dan WANG; Wenying NIE; Ming HE (Dianxin kexue)
Mobile intelligent terminal is the key entry to the internet services.Combining mobile intelligent terminal with office platform becomes a new mode of mobile OA,which is able to overcome the space-time limitation of traditional office model.To improve the efficiency of management and work,and to ensure the security of data,the security requirements of mobile OA were analyzed,a secure and controllable office system for mobile intelligent terminal also could be designed.The system structure,security function module,and business process were introduced,as well as the main function of mobile OA system was realized.By providing the unified management for mobile devices,data security based on licensing and use-control could be achieved.